Answer:
5y + 20
Step-by-step explanation:
5 (y+ 4) =
5(y) + 5(4) =
5y + 20
<em>Hope that helps!</em>
<em>-Sabrina</em>
Answer:
4 a+8 ab+8b
Step-by-step explanation:
8 a-4 a+6ab+2ab+5 b+3 b
4 a+8 ab+8b
The result of multiplying the polynomials is (2x + 3) (-x + 2y - 4) = -2x² + 4xy - 11x + 6y - 12
<h3>How to multiply the
polynomials?</h3>
The polynomial expression is given as
(2x + 3) (-x + 2y - 4)
Expand the brackets in the above polynomial expression
So, we have
(2x + 3) (-x + 2y - 4) = 2x * (-x + 2y - 4) + 3 * (-x + 2y - 4)
Open the brackets in the above polynomial expression
So, we have
(2x + 3) (-x + 2y - 4) = -2x² + 4xy - 8x + -3x + 6y - 12
Evaluate the like terms in the above polynomial expression
So, we have
(2x + 3) (-x + 2y - 4) = -2x² + 4xy - 11x + 6y - 12
Hence, the solution is -2x² + 4xy - 11x + 6y - 12
Read more about polynomials at
brainly.com/question/17517586
#SPJ1
Answer:
5/12
Step-by-step explanation:
1/4 + 1/6 = (6+4)/24 = 10/24 = 5/12
why +1/6?
because: - (-) = +